Data detection algorithms specially designed for the downlink of CDMA mobile radio systems - Klein, A. (1997 IEEE 47th Vehicular Technology Conference. Technology in Motion, 1997)
In this paper, suboptimum data detection algorithms specially designed for the downlink of CDMA systems are presented which take into account the downlink-specific system characteristics. These algorithms are based on the zero forcing (ZF) criterion and the minimum mean square error (MMSE) criterion, respectively. Basically, they consist of a channel equalizer followed by a code-matched filter. They allow to exploit the multipath diversity of the mobile radio channel. Only the CDMA code used for transmission to the mobile station of interest is needed at the receiver and only the data symbols addressed to that individual mobile station are detected. The computational complexity is independent of the number of active users, which allows to provide mobile terminals of small size and weight with low power consumption. The algorithms are applied to the downlink of a TDMA/CDMA system concept. The algorithms specially designed for the downlink situation lead to a significant system performance enhancement as compared with the conventional matched filter or Rake receiver and to a slightly worse system performance than ZF- and MMSE-based joint detection algorithms which are applicable also in the uplink and which require that all CDMA codes presently used for transmission to the active mobile stations are known at each of these mobile stations.